Method for marking fiber micro-plastic by using up-conversion nanoparticles and application
Through electrospinning technology, the rare earth-doped upconverted nanoparticles are combined with fiber microplastics, which solves the problem of insufficient stability and detection signal-to-noise ratio of fiber microplastic markers, and achieves high sensitivity in vivo detection and analysis of biological in vivo.
Patent Information
- Application Number
- CN202411625934.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to effectively label fiber microplastics, especially during migration and transformation in biological organisms, the stability of the marker and detection signal-to-noise ratio are insufficient.
Rare-earth-doped upconverted nanoparticles (UCNPs) are used as markers, and UCNPs are dispersed with polyacrylonitrile (PAN) powder through electrospinning technology to form labeled fiber microplastics. The method includes solvothermal synthesis of UCNPs, encapsulating an inert shell, dispersing it in the spinning liquid, preparing a fiber membrane by an electrospinning-high-speed roller system, and obtaining uniformly sized labeled fiber microplastics by frozen slices.
High sensitivity detection of fiber microplastics is achieved, the interference of autofluorescence of biological tissues is reduced, the stability and luminous intensity of markers are improved, and visual observation and quantitative analysis can be achieved in biological bodies.
Smart Images

Figure CN119505463A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the labeling of microplastics, and specifically to a method and application of labeling fiber microplastics by using upconversion nanoparticles. Background Art
[0002] Microplastics (MPs), as an emerging environmental pollutant, are widely present in aquatic ecosystems such as oceans and rivers. MPs have potential toxic effects on aquatic organisms and even the entire ecosystem. MPs have various forms in the environment, among which fibrous microplastics have attracted much attention due to their wide distribution and potential high toxicity. However, due to the characteristics of microplastics themselves, their migration and transformation process in organisms is difficult to track. In order to explore the dynamics of MPs in organisms, it is generally necessary to label MPs. Traditional microplastic labeling methods, such as Nile red staining and isotope labeling, have certain limitations. Nile red staining is easily interfered by biological autofluorescence, and the dye is easy to fall off; the isotope labeling method has problems such as insufficient stability of the marker and high detection cost. Especially in the gastrointestinal tract of higher animals, the stability and sustainability of the marker are difficult to guarantee.
[0003] Upconversion nanoparticles (UCNPs) are nanomaterials with unique upconversion luminescence properties doped with lanthanide ions. UCNPs have shown broad application prospects in the field of bioimaging due to their own characteristics. Compared with traditional fluorescent dyes, upconversion nanoparticles have the ability to be excited by near-infrared, which can weaken the spontaneous fluorescence interference of biological tissues to a certain extent. In particular, they also have a long fluorescence lifetime. The use of time-gated imaging (TGI) technology to collect fluorescence signals can further significantly reduce the background fluorescence interference of biological tissues and improve the imaging signal-to-noise ratio. In addition, the rare earth elements in UCNPs can be used as internal standards, and the markers can be analyzed quantitatively with high sensitivity using a plasma mass spectrometer. At present, the application of UCNPs as markers to fiber microplastics needs to overcome the following problems: UCNPs are usually used in a smaller particle size (10-100nm) for bioimaging or other nanotechnology fields, but the small particle size may lead to an increase in surface energy traps, further reducing the luminescence efficiency; in addition, UCNPs are not stable enough in some complex environments. For example, in vivo or in different solution environments, UCNPs may undergo photobleaching, surface degradation or chemical reactions, resulting in attenuation of the fluorescence signal, limiting their long-term use; finally, how to effectively combine UCNPs with fibrous microplastics to obtain fibrous microplastics with uniform size and no significant changes in properties is an urgent problem that needs to be solved in current research. Summary of the invention
[0004] The purpose of the present invention is to provide a method and application of labeling fiber microplastics using upconversion nanoparticles.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for labeling fiber microplastics using upconversion nanoparticles, wherein rare earth-doped UCNPs and PAN powder are dispersed in a dispersion to obtain a spinning solution, and the fiber microplastics are labeled with upconversion nanoparticles through an electrospinning-high-speed drum system.
[0007] Furthermore, rare earth-doped UCNPs wrapped with inert shells and PAN powder are dispersed in a dispersion in a certain proportion to obtain a spinning solution, and an orderly arranged fiber membrane is obtained through an electrospinning-high-speed drum system. Finally, uniform-sized upconversion nanoparticles labeled fiber microplastics are obtained through cryosectioning.
[0008] Specifically: (1) A solvothermal method is used to synthesize rare earth-doped UCNPs coated with an inert shell; (2) The obtained UCNPs and PAN powder are dispersed in a dispersion according to a certain ratio to obtain a spinning solution, and the fibers are arranged in an orderly manner through an electrospinning-high-speed drum system to obtain a fiber membrane.
[0009] The step (2) disperses the obtained UCNPs and PAN powder in a dispersion liquid in a certain ratio to obtain a spinning solution, and arranges the fiber microplastics in an orderly manner to form a fiber membrane through an electrospinning-high-speed drum system; further freeze-slices and cleans and purifies the fiber membrane to obtain upconversion nanoparticle-labeled fiber microplastics with uniform size and no impurities.
[0010] The rare earth-doped UCNPs are prepared by mixing rare earth chloride with oleic acid (OA) and octadecene (ODE) and heating to 130°C under vacuum stirring to form a uniform solution. After cooling to room temperature, sodium hydroxide (NaOH) and ammonium fluoride (NH4F) are added to the system and vacuum stirring is continued. The mixed solution is then heated at 290-300°C for 1.5-1.6h under argon conditions, and the nanoparticles are collected. An inert shell layer is then coated on the surface of the particles to reduce surface defects. After coating, the particles are dispersed in cyclohexane for standby use.
[0011] The mass volume ratio of the rare earth chloride, oleic acid (OA) and octadecene (ODE) is 0.5-1:18-22:48-52; wherein the rare earth chloride is LuCl3, YbCl3 and ErCl 3, The mass ratio is 18-24:5-6:0.5-1; the mass ratio of sodium hydroxide (NaOH) and ammonium fluoride (NH4F) to rare earth chloride (LuCl3) in the system is 0.05-0.2:0.1-0.2:0.2:0.3.
[0012] The coating of the inert shell layer is to mix rare earth chloride, oleic acid (OA) and octadecene (ODE) and stir and heat to 130°C in vacuum to form a uniform solution, and then disperse the collected nanoparticles in a cyclohexane solution, add the formed uniform solution thereto, and perform epitaxial growth in a flask, and stir the flask under vacuum for 15 minutes. Finally, the mixed solution is rapidly heated to 290-300°C for 1.5 hours under an argon atmosphere, so that the surface of the nanoparticles is coated with an inert shell layer.
[0013] The rare earth chloride is LuCl3, YbCl 3、 One or more of ErCl3; the mass volume ratio of the rare earth chloride, oleic acid (OA) and octadecene (ODE) is 0.5-4:50-70:140-160.
[0014] The step (2) is to mix the UCNPs obtained in the step (1) with PAN powder according to a mass ratio, and after mixing, uniformly disperse them in N,N-dimethylformamide (DMF) to obtain an electrospinning solution; wherein the mass ratio of the UCNPs obtained in the step (1) to the PAN powder is 5-15:80-100, preferably 6-7:90-100; the PAN powder has a molecular weight of 150,000; the concentration of the PAN powder in the dispersion is in the range of 8%-12wt%, preferably 10%-11wt%. The loading rate of UCNPs in the fiber microplastic is controlled by controlling the doping ratio of UCNPs to PAN powder, and the PAN powder has a molecular weight of 150,000. The concentration of the spinning solution is the concentration of PAN powder dissolved in DMF, and the concentration of the spinning solution is in the range of 8%-12%. Controlling the concentration of the spinning solution is one of the factors controlling the fiber diameter.
[0015] The electrospinning method is to move forward at a speed of 1-1.5 mL / h, and apply a voltage of 20-24 kV, preferably 20-22 kV. Controlling the voltage is one of the factors controlling the fiber diameter. The distance between the collector and the needle is 14-15 cm, and the temperature and humidity are controlled throughout the spinning process, the temperature is maintained at 23-25° C., and the humidity is maintained at 50%-55%.
[0016] An application of the method, which is application of the method in tracking and identifying fibrous microplastics in the environment.
[0017] The advantages of the present invention are
[0018] 1. The present invention uses upconversion nanoparticles as markers, which can effectively reduce the interference of spontaneous fluorescence of biological tissues and achieve high-sensitivity detection of labeled fiber microplastics. At the same time, after the surface of the upconversion nanoparticles is coated with an inert shell, its surface defects are suppressed, greatly improving the luminescence intensity. The fiber microplastics obtained by the technology of the present invention can be applied to the body to achieve visual observation and quantitative analysis, providing a powerful tool for studying the biological effects of fiber microplastics;
[0019] 2. The present invention uses electrospinning technology to encapsulate rare earth upconversion nanoparticles inside fiber microplastics, overcoming the problems of easy detachment and insufficient stability of traditional labeling technology. In addition, UCNPs inside the fiber are not easily disturbed by the external environment, ensuring their stability.
[0020] 3. The orderly arranged fiber membrane obtained by the present invention can obtain fiber microplastics with uniform length and diameter and free of impurities after freeze cutting and purification steps. The method provided by the present invention can achieve controllable length and diameter, and can meet the requirements for fiber microplastics in different studies. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a transmission electron microscope (TEM) image of the upconversion nanoparticles synthesized in Example 1;
[0022] Figure 2 This is a scanning electron microscope (SEM) image of the labeled fiber microplastics in Example 1;
[0023] Figure 3 This is a transmission electron microscope (TEM) image of the labeled fiber microplastics in Example 1;
[0024] Figure 4 This is a scanning electron microscope (SEM) image of the labeled fiber microplastics in Example 2;
[0025] Figure 5 This is a transmission electron microscope (TEM) image of the labeled fiber microplastics in Example 2;
[0026] Figure 6 To count the upconversion nanoparticle labeling rate of the fiber in the transmission electron microscope field of view of Example 1 (left figure) and Comparative Example 1 (right figure);
[0027] Figure 7 This is a time-gated imaging (TGI) image of labeled fiber microplastics in a stomach tissue slice of a living organism in Example 3;
[0028] Figure 8 The rare earth leakage rate of the labeled fiber microplastics provided in the embodiment of the present invention in a simulated gastrointestinal fluid environment;
[0029] Fig. 9This is a time-gated imaging (TGI) image of the labeled fibers provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0030] The specific implementation of the present invention is further described below in combination with the technical solution. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative achievements belong to the protection scope of the present invention.
[0031] The present invention doped rare earth upconversion nanoparticles (UCNPs) into PAN spinning solution and labeled fiber microplastics by electrospinning, which has higher sensitivity and stability. Using this method to label fiber microplastics can realize its application potential in tracking in vivo. The method of the present invention provides a new technical means for studying the migration and transformation rules of MPs in the environment, which helps to gain a deeper understanding of the potential impact of MPs on the ecological environment and human health.
[0032] The method for preparing upconversion nanoparticle-labeled polyacrylonitrile fiber microplastics of the present invention effectively solves the existing problems and verifies its feasibility through experiments.
[0033] The labeled fiber microplastics prepared by the present invention have excellent upconversion luminescence properties, can effectively reduce the interference of spontaneous fluorescence of biological tissues, and detect the distribution of labeled fiber microplastics in vivo through time-gated imaging technology; the rare earth elements in UCNPs can be used as element labels, and high-sensitivity quantitative analysis can be performed using a plasma mass spectrometer; and the UCNPs are firmly embedded in the fiber microplastics through electrospinning technology to ensure the stability of the markers, and the diameter of the fiber microplastics can be precisely controlled by adjusting the spinning solution concentration and the spinning machine voltage.
[0034] Example 1: A method for preparing UCNPs labeled fiber microplastics with an average diameter of 200 nm;
[0035] (1) Rare earth chloride (0.78mmol LuCl3, 0.2mmol YbCl3, 0.02mmol ErCl3) was mixed with 6mol oleic acid (OA) and 15mol octadecene (ODE), and heated and stirred at 130°C in a three-necked round-bottom flask. After cooling to room temperature, 2.5mmol sodium hydroxide (NaOH) and 4mmol ammonium fluoride (NH4F) were added to the flask and stirred in vacuum for 15min. The mixed solution was heated to 290-300°C under argon for 1.5h, and the obtained nanoparticles were collected and dispersed in cyclohexane.
[0036] Finally, the obtained nanoparticles were coated with an inert shell to reduce surface defects. The specific steps were as follows: 1 mmol LuCl3 was mixed with 6 ml OA and 15 ml ODE in a three-necked round-bottom flask, 6 mL cyclohexane solution with dispersed nanoparticles was added to the flask, the reaction conditions were the same as the above steps, and the obtained UCNPs were collected (see Figure 1 ).Depend on Figure 1 It can be seen that the particle size of UCNPs is relatively uniform, and there is no obvious depression on the surface.
[0037] (2) The UCNPs obtained in step (1) were mixed with PAN powder in a mass ratio of 7:100, wherein the mass fraction of PAN was 11%. The two were then dispersed in DMF and ultrasonically dispersed at room temperature for 30 minutes to obtain a spinning solution with a PAN concentration of 11%. The spinning solution was sucked in using a 5mL syringe equipped with a metal needle, the needle specification was 23G, and it was pushed forward at a speed of 1mL / h, while a voltage of 20kV was applied. The cylindrical collector rotated at a speed of 3000r / h, and the distance between the collector and the needle was set to 15cm. The temperature was maintained at 25°C and the relative humidity was 50% during the entire spinning process. The collected fibers were coated on release paper. After the spinning was completed, the release paper coated with the fiber membrane was removed and placed in a vacuum oven at 50°C for 1h to obtain a fiber membrane.
[0038] (3) The fiber membrane obtained in step (2) is cut into stripes of uniform length and width, folded into rectangular strips, and then each strip is embedded in a silicon mold with an OCT embedding agent and frozen at -20°C. The frozen column is cryosectioned at -20°C with a cutting step of 1 μm using a cryostat to obtain fiber segments. The obtained fiber segments are dissolved in deionized water, stirred at 60°C for 24 hours, and the embedding agent is washed away. The solution is then filtered through organic filter membranes with pore sizes of 50 μm, 20 μm, and 0.45 μm, respectively, and washed with ethanol during the filtration process. The filtration process is repeated three times. The cleaned fiber microplastics are observed using a scanning electron microscope (see Figure 2 ).
[0039] As can be seen from the figure, the surface of the fiber microplastics labeled with upconversion nanoparticles is smooth, without obvious protrusions, and the length is relatively uniform. Figure 3 The transmission electron microscopy image shows the distribution of UCNPs inside PAN fibers. The results show that UCNPs are successfully loaded inside PAN fibers.
[0040] Comparative Example 1: A method for preparing UCNPs labeled fiber microplastics with an average diameter of 500 nm;
[0041] (1) The UCNPs obtained in Example 1 were mixed with PAN powder in a mass ratio of 7:100, wherein the mass fraction of PAN was 13%. The two were then dispersed in DMF and ultrasonically dispersed at room temperature for 30 min to obtain a spinning solution with a PAN concentration of 13%. The spinning solution was inhaled using a 5 mL syringe equipped with a metal needle, the needle specification was 23G, and it was pushed forward at a speed of 1 mL / h, while applying a voltage of 18 kV. The cylindrical collector rotated at a speed of 3000 r / h, the distance between the collector and the needle was 15 cm, and the temperature was maintained at 25 ° C and the relative humidity was 50% during the entire spinning process. The collected fibers were coated on release paper. After the spinning was completed, the release paper coated with the fiber membrane was removed and placed in a vacuum oven at 50 ° C for 1 hour to obtain a fiber membrane.
[0042] (2) The fiber membrane obtained in step (1) is cut into stripes of uniform length and width, folded into rectangular strips, and then each strip is embedded in a silicon mold with an OCT embedding agent and frozen at -20°C. The frozen column is cryosectioned at -20°C with a cutting step of 1 μm using a cryostat to obtain fiber segments. The obtained fiber segments are dissolved in deionized water, stirred at 60°C for 24 hours, and the embedding agent is washed away. The solution is then filtered through organic filter membranes with pore sizes of 50 μm, 20 μm, and 0.45 μm, respectively, and washed with ethanol during the filtration process. The filtration process is repeated three times. The cleaned fiber microplastics are observed using a scanning electron microscope (see Figure 4 ). As can be seen from the figure, the fiber surface morphology is not significantly different from that of the experimental case 1, and the length is uniform, but the fiber diameter is significantly increased compared with the implementation case 1, which is due to the adjustment of the spinning solution concentration and the spinning voltage. Figure 5 The transmission electron microscopy image shows the distribution of UCNPs inside the PAN fiber microplastics. The results show that UCNPs were successfully loaded inside the PAN fiber, and the loading amount of UCNPs inside the fiber increased compared with the implementation case 1, which was due to the increase in fiber diameter.
[0043] The transmission electron microscopy images of the fiber microplastics obtained in the above examples and the comparative examples were compared and measured using Fiji ImageJ software. The upconversion nanoparticles obtained in the comparative example were mostly concentrated inside a single fiber, and the overall fiber labeling rate was relatively low. By counting the labeling rate of fibers within the field of view of the electron microscope image (see Figure 6 ), Comparative Example 1 is only about 20%, while Example 1 reaches more than 70%, which is much lower than Example 1.
[0044] Example 2: Application of UCNPs labeling fiber microplastics;
[0045] To verify the labeling and tracing ability of the prepared UCNPs-labeled fiber microplastics in vivo, 10 quails aged 80-100 days were selected as experimental animals, with a body weight range of 140-170g. The quails were purchased from a farm in Qingdao. During the experiment, the quails were fed with ordinary feed, and a certain amount of fiber microplastic suspension labeled with upconversion nanoparticles was added to the drinking water for continuous exposure for 10 days. After the experiment, the stomach tissue of the quail was frozen and sectioned, and the distribution of the labeled fiber microplastics in the tissue was observed under a time-gated fluorescence microscope. Figure 7 As shown, the green fluorescence is the TGI signal of the labeled fiber microplastics. In addition, the luminescence of the PAN fiber membrane was observed under a time-gated fluorescence microscope (see Fig. 9 ), it can be seen from the figure that the fiber prepared by this method has excellent fluorescence effect.
[0046] In order to evaluate the stability of labeled fiber microplastics in a simulated digestive tract environment, an in vitro gastrointestinal simulation model of birds and poultry was constructed. The specific steps are as follows: 2g of pepsin and 11.68g of NaCl were weighed, dissolved in deionized water, and the pH was adjusted to 3 with 3mol / L hydrochloric acid to prepare artificial avian gastric juice. Subsequently, 100mL of gastric juice was taken, 0.35g of bile salts and trypsin were added respectively, and the pH was adjusted to 7 with 0.4% NaOH solution to simulate the gastrointestinal fluid environment.
[0047] A certain amount of labeled fiber microplastics was placed in 10 ml simulated gastrointestinal fluid to simulate the static digestion process. Samples were taken at 0 h, 24 h, 72 h, 168 h, 240 h and 360 h, and centrifuged at 10,000 rpm for 15 min using a 3 kDa ultrafiltration tube to separate free Lu. After the ultrafiltrate was acidified with 1% nitric acid, the content of Lu was detected by inductively coupled plasma mass spectrometry (ICP-MS) to obtain the leakage of rare earth element Lu (see Figure 8 ). The results showed that the leakage rate of Lu element was always less than 0.1%, which indicates that the upconversion nanoparticles have good stability in fibrous microplastics.
Claims
1. A method for labeling fiber microplastics using upconversion nanoparticles, characterized in that: Rare earth-doped UCNPs and PAN are dispersed in a dispersion to obtain a spinning solution, and the upconversion nanoparticles are used to label fiber microplastics through an electrospinning-high-speed drum system.
2. The method for labeling fiber microplastics using upconversion nanoparticles according to claim 1, characterized in that: (1) Rare earth-doped UCNPs coated with an inert shell were synthesized by a solvothermal method; (2) The obtained UCNPs were mixed with PAN powder and dispersed in a dispersion to obtain a spinning solution, and the fiber microplastics were labeled with upconversion nanoparticles through an electrospinning-high-speed drum system.
3. The method for labeling fiber microplastics using upconversion nanoparticles according to claim 2, characterized in that: The step (2) obtains an orderly arranged fiber membrane through an electrospinning-high-speed drum system; the fiber membrane is cryosectioned and purified to obtain upconversion nanoparticle-labeled fiber microplastics.
4. The method for labeling fiber microplastics using upconversion nanoparticles according to claim 2, characterized in that: The rare earth doped UCNPs coated with an inert shell are prepared by mixing rare earth chloride with oleic acid (OA) and octadecene (ODE), stirring and heating to 130°C under vacuum to form a uniform solution. After cooling to room temperature, sodium hydroxide (NaOH) and ammonium fluoride (NH4F) are added to the system and vacuum stirring is continued. The mixed solution is then heated at 290-300°C for 1.5-1.6h under argon conditions, the nanoparticles are collected, and then the surface of the particles is coated with an inert shell. After coating, the particles are dispersed in cyclohexane for standby use.
5. The method for labeling fiber microplastics using upconversion nanoparticles according to claim 4, characterized in that: The mass volume ratio of the rare earth chloride, oleic acid (OA) and octadecene (ODE) is 0.5-1:18-22:48-52; wherein the rare earth chloride is LuCl3, YbCl3 and ErCl 3, The mass ratio is 18-24:5-6:0.5-1; the mass ratio of sodium hydroxide (NaOH) and ammonium fluoride (NH4F) to rare earth chloride (LuCl3) in the system is 0.05-0.2:0.1-0.2:0.2-0.
3.
6. The method for labeling fiber microplastics using upconversion nanoparticles according to claim 4, characterized in that: The encapsulating inert shell layer comprises the following steps: mixing rare earth chloride, oleic acid (OA) and octadecene (ODE) under vacuum stirring and heating to 130° C. to form a uniform solution; then dispersing the collected nanoparticles in a cyclohexane solution, adding the formed uniform solution thereto, and performing epitaxial growth in a flask, while the flask is kept under vacuum stirring for 15 minutes; finally, rapidly heating the mixed solution to 290-300° C. under an argon atmosphere for 1.5 hours to form an encapsulating inert shell layer on the surface of the nanoparticles.
7. The method for labeling fiber microplastics using upconversion nanoparticles according to claim 6, characterized in that: The rare earth chloride is LuCl3, YbCl 3、 One or more of ErCl3; the mass volume ratio of the rare earth chloride, oleic acid (OA) and octadecene (ODE) is 0.5-4:50-70:140-160; the mass volume ratio of the rare earth chloride to the nanoparticles is 0.5-4:10-12.
8. The method for labeling fiber microplastics using upconversion nanoparticles according to claim 2, characterized in that: The step (2) is to mix the UCNPs obtained in the step (1) with PAN powder according to a mass ratio, and after mixing, evenly disperse them in N,N-dimethylformamide (DMF) to obtain a spinning solution; wherein the mass ratio of the UCNPs obtained in the step (1) to the PAN powder is 5-15:80-100, and the PAN powder has a molecular weight of 150,000; and the concentration of the PAN powder in the dispersion is in the range of 8%-12wt%.
9. The method for labeling fiber microplastics using upconversion nanoparticles according to claim 2, characterized in that: The electrospinning method is to advance at a speed of 1-1.5 mL / h, apply a voltage of 20-24 kV, and the distance between the collector and the needle is 14-15 cm. The temperature and humidity are controlled throughout the spinning process, the temperature is maintained at 23-25° C., and the humidity is maintained at 50%-55%.
10. An application of the method according to claim 1, characterized in that: Application of the method in fiber microplastic labeling and tracing.